A crown-group cnidarian from the Ediacaran of Charnwood Forest, UK - Dunn, FS; Kenchington, CG; Parry, LA; Clark, JW; Kendall, RS; Wilby, PR (Springer Nature, 2022)
Cnidarians are a disparate and ancient phylum, encompassing corals and jellyfish, and occupy both the pelagic and benthic realms. They have a rich fossil record from the Phanerozoic eon lending insight into the early history of the group but, although cnidarians diverged from other animals in the Precambrian period, their record from the Ediacaran period (635–542 million years ago) is controversial. Here, we describe a new fossil cnidarian—Auroralumina attenboroughii gen. et sp. nov.—from the Ediacaran of Charnwood Forest (557–562 million years ago) that shows two bifurcating polyps enclosed in a rigid, polyhedral, organic skeleton with evidence of simple, densely packed tentacles. Auroralumina displays a suite of characters allying it to early medusozoans but shows others more typical of Anthozoa. Phylogenetic analyses recover Auroralumina as a stem-group medusozoan and, therefore, the oldest crown-group cnidarian. Auroralumina demonstrates both the establishment of the crown group of an animal phylum and the fixation of its body plan tens of millions of years before the Cambrian diversification of animal life.